Continuity of care in acute survivorship phase, and short and long‐term outcomes in prostate cancer patients. Issue 16 (13th September 2021) - Chhatre, Sumedha; Malkowicz, S. Bruce; Jayadevappa, Ravishankar
Abstract: Continuity of care is important for prostate cancer care due to multiple treatment options, and prolonged disease history. We examined the association between continuity of care and outcomes in Medicare beneficiaries with localized prostate cancer, and the moderating effect of race using Surveillance, Epidemiological, and End Results (SEER) – Medicare data between 2000 and 2016. Continuity of care was measured as visits dispersion (continuity of care index or COCI), and density (usual provider care index or UPCI) in acute survivorship phase. Outcomes were emergency room visits, hospitalizations, and cost during acute survivorship phase and mortality (all‐cause and prostate cancer‐specific) over follow‐up phase. Higher continuity of care was associated with improved outcomes, and interaction between race and continuity of care was significant. Continuity of care during acute survivorship phase may lower the racial disparity in prostate cancer care. Future research can analyze the mechanism of the process.